Lingual Units Containing The Third Persona Pronoun In The Translated Text Of Buchori Hadith Contain Linguistic Ethics - Reistanti, Agustina Putri; Widodo, Widodo; Salama, Mahi Sultan (Sekolah Tinggi Agama Islam Muhammamdiyah Blora, 2024)
: The purpose of this research is to describe the role of filling the lingual unit that contains third personal pronouns in the text of buchorihadith translation which contains language ethics. The data of the research are in the form of the clause containing PP3 in the text of the buchorihadith translation which contains language ethics. The data collection method of this research is the observation and note-taking method. The method of data analysis used in this research is padan referential method. The result of this research is the role-filled lingual unit that contains third personal pronouns namely (1) the role of patient, (2) the role of origin, (3) the role of existence, (4) the role of the tool, (5) the role of designation, (6) the role of goals, (7) the role of experience, (8) the role of place, (9) the role of participant, and (10) the of attributive, (11) the role of described, (12) the role of actors, (13) the role of the recipient, (14) the role of known.